CT and MR imaging of the adrenal glands in ACTH-independent cushing syndrome. - Rockall, A; Babar, SA; Sohaib, SA; Isidori, A; Diaz-Cano, S; Monson, J; Grossman, AB; Reznek, R (2004)
Adrenocorticotropic hormone (ACTH)-independent hypercortisolism accounts for 15%-20% of cases of Cushing syndrome and always arises from primary adrenal disease. Computed tomographic (CT) and magnetic resonance (MR) imaging findings in 37 patients with primary adrenal Cushing syndrome were analyzed and correlated with pathologic findings. Hyperfunctioning adenomas (n = 24), together with functioning carcinomas (n = 10), accounted for 92% of cases. Adenomas had a significantly smaller mean size (3.5 vs 14.5 cm) and lower mean unenhanced CT attenuation value (11 vs 28 HU) than did carcinomas. The presence of necrosis, hemorrhage, and calcification favored a diagnosis of carcinoma. Six of 10 carcinoma patients had metastases at presentation. Two adenomas were seen within a myelolipoma, which was recognized at both CT and MR imaging due to its fat content, and two adenomas were of uncertain malignant potential. Bilateral disease--primary pigmented nodular adrenal dysplasia (PPNAD) (n = 2) and ACTH-independent macronodular adrenal hyperplasia (AIMAH) (n = 1)--had characteristic imaging features. In PPNAD, multiple tiny (2-5-mm) nodules were visible bilaterally, with no overall glandular enlargement and normal intervening adrenal tissue. In AIMAH, both glands were grossly enlarged and contained nodules up to 3 cm in diameter. Familiarity with the range of imaging appearances of the adrenal glands in primary adrenal Cushing syndrome may help establish the underlying diagnosis.